Elaborating the Derivational Morpheme in Students’ Thesis Acknowledgement in Higher Education - Eripuddin; Rahayu, Pipit; Kasyulita, Evi; Rasyidah, Ummi; Manalu, Nurapriani (Journal of Applied Linguistics, 2024)
The students are still finding difficulties in formatting the sentences in the thesis acknowledgments. This study aimed to find out the types of derivational morphemes and the function of derivational morphemes used in the students’ thesis acknowledgments. This study is qualitative descriptive research. The instrument of this study was the documentation. There were nine acknowledgments of the student’s thesis.  The data were analyzed by using the descriptively characteristic analysis. The result of the data analysis, the researcher found four types of derivational morphemes in the thesis acknowledgment, which are noun derivation, verb derivation, adjective derivation, and adverb derivation. In this study, researchers also found the types of derivation morphemes that are dominantly used and those that are rarely used. Thus, the derivational morpheme should be comprehended by the students to write the acknowledgments academically. Keywords : Derivational_morpheme; Acknowledgments; Higher_education